Existence of Solutions for Two-Point Boundary Value Problem of Fractional Differential Equations at Resonance - Lei Hu; Shuqin Zhang; Ailing Shi (International Journal of Differential Equations)
We establish the existence results for two-point boundary value problem of fractional differential equations at resonance by means of the coincidence degree theory. Furthermore, a result on the uniqueness of solution is obtained. We give an example to demonstrate our results.